On some problems in perturbation theory of smooth invariant tori of dynamical systems - Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
Problems related to perturbation theory of smooth invariant tori of dynamical systems in a n-dimensional Euclidean spaceR n are considered. The clarification of these problems plays an important role for perturbation theory suggested by the author in [1] and extends the scope of its application.